The Influence of Guided Discovery Learning Model Assisted by GeoGebra Software on Understanding Mathematical Concepts in Flat Shape Materials for Private MTs Darul Muttaqin Kandangan - Pratiwi AS, Tria Ayunda; Maryanti, Indra (Lembaga Riset Mutiara Akbar, 2022)
This study aims to determine whether there is an effect of guided discovery learning assisted by GeoGebra software on the understanding of mathematical concepts in the flat material of the Darul Muttaqin Kandangan students' private MTs. The population in this study were all students of class VIII MTs Swasta Darul Muttaqin Kandangan with a total of 90 students. While the sample used in this study was class VIII3 students of private MTs Darul Muttaqin cage with a total of 30 students. This research uses quantitative research and one-group pretest-posttest research design. The data analysis technique used in this research is the normality test using the Lilliefors test and hypothesis testing using the t test. Processing of data to be tested using Microsoft Excel program. The results of this study indicate that there is an influence of the guided discovery learning model assisted by GeoGebra software on the understanding of mathematical concepts in the flat wake material of the Darul Muttaqin Kandangan students' private MTs. This can be seen from the calculation of the hypothesis test using the t test with tcount > ttable, namely 5.32 > 1.701 at a significant level = 0.05. So, it can be said that H1 is accepted and H0 is rejected.